2022
DOI: 10.1021/acschembio.2c00796
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Design of a Potent and Specific Inhibitor against the Genomic Mutator APOBEC3A

Abstract: Nucleic acid structure plays a critical role in governing the selectivity of DNA- and RNA-modifying enzymes. In the case of the APOBEC3 family of cytidine deaminases, these enzymes catalyze the conversion of cytosine (C) to uracil (U) in single-stranded DNA, primarily in the context of innate immunity. DNA deamination can also have pathological consequences, accelerating the evolution of viral genomes or, when the host genome is targeted by either APOBEC3A (A3A) or APOBEC3B (A3B), promoting tumor evolution lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…41 DNA hairpins with short loops have also been shown to provide selective inhibitors of A3A when the target dC in the loop was changed to dZ-derivatives. [42][43][44] We also demonstrated that dZ and THU as free nucleosides did not inhibit A3 enzymes, which indicates that ssDNA delivers dZ into the active site of A3. 17 In the past, the diazepinone riboside was described as a more powerful inhibitor of CDA than dZ (K i = 25 nM for 1,3diazepin-2-one [31][32][33][34][35] and 2.9 µM for dZ).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…41 DNA hairpins with short loops have also been shown to provide selective inhibitors of A3A when the target dC in the loop was changed to dZ-derivatives. [42][43][44] We also demonstrated that dZ and THU as free nucleosides did not inhibit A3 enzymes, which indicates that ssDNA delivers dZ into the active site of A3. 17 In the past, the diazepinone riboside was described as a more powerful inhibitor of CDA than dZ (K i = 25 nM for 1,3diazepin-2-one [31][32][33][34][35] and 2.9 µM for dZ).…”
Section: Introductionmentioning
confidence: 80%
“…41 DNA hairpins with short loops have also been shown to provide selective inhibitors of A3A when the target dC in the loop was changed to dZ-derivatives. 42–44 We also demonstrated that dZ and THU as free nucleosides did not inhibit A3 enzymes, which indicates that ssDNA delivers dZ into the active site of A3. 17…”
Section: Introductionmentioning
confidence: 83%
“…Prior studies have shown that linear ssDNA substrates with 2-deoxyzebularine (dZ) and 5-fluoro-dZ (FdZ) in place of the target cytosine are weak inhibitors of A3A (and A3B) [30][31][32] . Additional work by our group and others has shown greater inhibition of A3A in vitro with pre-formed U-shaped, hairpin dZ and FdZ transition-state trapping oligonucleotides [33][34] . Here, we use X-ray crystallography to reveal the first high-resolution structures of wildtype A3A-inhibited complexes and demonstrate the underlying mechanism of inhibition.…”
Section: Introductionmentioning
confidence: 77%
“…Another area that is potentially available is in the realm of enzyme inhibition. Classical inhibitors have either been unreactive substrate mimics, 152 mechanism-based chemistry inhibitors, 153 or transition state inhibitors. 154 There has been expanded interest in finding ways to inhibit enzymes remote from the active site (to avoid mutational escape from inhibition, for example).…”
Section: Discussionmentioning
confidence: 99%